Cryptocurrency; the new unleashed financial instrument, should it be regulated - Ibrahim, Omar (Humanities Journal of University of Zakho, 2024)
The decentralized anonymous cryptocurrency is a new kind of technology that can be used for many purposes such as transferring money and investing. However, they do not have a legal entity that is in charge monitoring its uses. Its extraordinary rise raises critical questions such as, should we regulate it or ban it? Since its purposes have been converted from an anonymous payment system to a tool that is used in illegal actions and undermining financial standards. This paper seeks CC regulation options. Plus, it attempts to lay out the various risks they pose and benefits they bring with the technology they use (blockchain). The objective is to investigate which approach will be more reasonable for the country’s conditions. The regulators will try to convince CC service providers to obey rules and operate under official standards, while banners restrict the new instrument’s integration with the financial system. The study relied on the descriptive approach to achieve its objectives. The recent literature and publications of the most important related bodies around the world were reviewed. Findings reveal that it is too early for CCs to be considered legal tender. Moreover, both approaches could be adopted according to the country’s conditions. Plus, alternatives may have their say. Some suggestions are made for local agencies and investors.